Bacteroides thetaiotaomicron Starch Utilization Promotes Quercetin Degradation and Butyrate Production by Eubacterium ramulus - Rodriguez-Castaño, Gina Paola; Dorris, Matthew R.; Liu, Xingbo; Bolling, Bradley W.; Acosta-Gonzalez, Alejandro; Rey, Federico E. (Frontiers in Microbiology, 2019)
Consumption of flavonoids has been associated with protection against cardiovascular and neurodegenerative diseases. Most dietary flavonoids are subjected to bacterial transformations in the gut where they are converted into biologically active metabolites that are more bioavailable and have distinct effects relative to the parent compounds. While some of the pathways involved in the breakdown of flavonoids are emerging, little it is known about the impact of carbon source availability and community dynamics on flavonoid metabolism. This is relevant in the gut where there is a fierce competition for nutrients. In this study, we show that metabolism of one of the most commonly consumed flavonoids, quercetin, by the gut-associated bacterium Eubacterium ramulus is dependent on interspecies cross-feeding interactions when starch is the only energy source available. E. ramulus can degrade quercetin in the presence of glucose but is unable to use starch for growth or quercetin degradation. However, the starch-metabolizing bacterium Bacteroides thetaiotaomicron, which does not metabolize quercetin, stimulates degradation of quercetin and butyrate production by E. ramulus via cross-feeding of glucose and maltose molecules released from starch. These results suggest that dietary substrates and interactions between species modulate the degradation of flavonoids and production of butyrate, thus shaping their bioavailability and bioactivity, and likely impacting their health-promoting effects in humans.